The Effect of Indigo (Indigofera tinctoria L.) Waste on Growth Performance, Digestibility, Rumen Fermentation, Hematology and Immune Response in Growing Beef Cattle - Nirawan Gunun; Chatchai Kaewpila; Waroon Khota; Sineenart Polyorach; Thachawech Kimprasit; Wasana Phlaetita; Anusorn Cherdthong; Metha Wanapat; Pongsatorn Gunun (My University, 2022)
This experiment was conducted to assess the effect of indigo waste on the feed intake, digestibility, rumen fermentation, hematology, immune response and growth performance in growing beef cattle. Twenty crossbred beef cattle with an initial body weight (BW) of 145 ± 11 kg were fed four levels of indigo waste for 90 days in a trial. Additions of indigo waste at 0%, 10%, 20% and 30% in a concentrate diet using a completely randomized design (CRD). Cattle were fed concentrate at 1.8% BW, with rice straw fed ad libitum. The concentrate intake decreased linearly (p = 0.01) with the addition of indigo waste. The supplementation with indigo waste reduced dry matter (DM) and organic matter (OM) digestibility cubically (p = 0.03 and p = 0.02, respectively), while increasing neutral detergent fiber (NDF) digestibility cubically (p = 0.02). The final BW of beef cattle decreased linearly (p = 0.03) with the addition of indigo waste. The inclusion of indigo waste decreased the average daily gain (ADG) and gain-to-feed ratio (G:F) linearly (p < 0.01) from 0 to 90 days. The nutrient digestibility, ADG and G:F of beef cattle fed 10% indigo waste in the diet was similar when compared with the control (0% indigo waste). The ruminal pH, ammonia-nitrogen (NH3-N) and total volatile fatty acid (VFA) concentrations were similar among treatments (p > 0.05). The proportion of acetate increased linearly (p < 0.01) but propionate decreased linearly (p < 0.01), resulting in an increase in the acetate to propionate ratio (p < 0.01) when cattle were fed with indigo waste supplementation. Increasing indigo waste levels did not influence blood urea nitrogen (BUN) levels, hematological parameters or immune responses (IgA, IgM and IgG) (p > 0.05). In conclusion, the inclusion of indigo waste at 10% in a concentrate diet did not have a negative effect on feed intake, nutrient digestibility, rumen fermentation, hematology, immune function or growth performance in growing beef cattle.
Keywords: Beef Cattle; Neutral Detergent Fiber; Completely randomized design; Ruminant Nutrition and Digestive Physiology